Cerebral small vessel disease and perihematomal edema formation in spontaneous intracerebral hemorrhage - Cliteur, Maaike P.; Sondag, Lotte; Wolsink, Axel; Rasing, Ingeborg; Meijer, F. J. A.; Jolink, Wilmar M. T.; Wermer, Marieke J. H.; Klijn, Catharina J. M.; Schreuder, Floris H. B. M. (Frontiers in Neurology, 2022)
Objective: Blood-brain barrier (BBB) dysfunction is implicated in the pathophysiology of cerebral small vessel disease (cSVD)-related intracerebral hemorrhage (ICH). The formation of perihematomal edema (PHE) is presumed to reflect acute BBB permeability following ICH. We aimed to assess the association between cSVD burden and PHE formation in patients with spontaneous ICH. Methods: We selected patients with spontaneous ICH who underwent 3T MRI imaging within 21 days after symptom onset from a prospective observational multicenter cohort study. We rated markers of cSVD (white matter hyperintensities, enlarged perivascular spaces, lacunes and cerebral microbleeds) and calculated the composite score as a measure of the total cSVD burden. Perihematomal edema formation was measured using the edema extension distance (EED). We assessed the association between the cSVD burden and the EED using a multivariable linear regression model adjusting for age, (log-transformed) ICH volume, ICH location (lobar versus non-lobar), and interval between symptom onset and MRI. Results: We included 85 patients (mean age 63.5 years, 75.3% male). Median interval between symptom onset and MRI imaging was 6 days (IQR 1-19). Median ICH volume was 17.0 mL (IQR 1.4-88.6), and mean EED was 0.54 cm (SD 0.17). We found no association between the total cSVD burden and EED (B=-0.003, 95% CI -0.003 to 0.03, p=0.83), nor for any of the individual radiological cSVD markers. Conclusion: We found no association between the cSVD burden and PHE formation. This implies that mechanisms other than BBB dysfunction are involved in the pathophysiology of PHE.